Cooperare și conflict în relațiile industriale: rolul dialogului social - Dumitru, Mihai (Calitatea Vieții, 2010)
Industrial relations, more than other social life areas, are fundamenting themselves on cooperation, cohesion and orienting their behaviour towards an economic (common) finality. From time to time, the structures of cooperation are melting, employees and employers finding themselves on opposite sides. Workers have many options of action – individual or collective – to resolve work miscontents. The collective option and the starting of the work conflict are depending on a variety of variables: the sector of activity (public or private). The type of industry, the size of the firm (number of employees), the degree of workers’ organization level (the existing number of unions), the type of management, the motive of divergences (wages, working conditions, etc.), and the proportion of miscontent workers, etc. Statistics on work conflicts are revealing only the “tip of the iceberg”. But conflicts have also a hidden dimension, detectable only by social research. It’s not just about ruptures and clivager in the social structure. The population’s perception on conflicts between employees and manager (employers), when shared by large social segments, are becoming social constructs, resilient to change and which are influencing the behaviour the principal actors within the industrial relations.